The Effectiveness of Murrotal Al-Qur'an Therapy on the Sleep Quality of Babies Aged 3-6 Months - Puspitarati, Triya (HM Publisher, 2024)
Sleep disorders are a common problem in babies, including babies aged 3-6 months. Murrotal Al-Qur'an therapy is a therapy that can be used to treat sleep disorders in babies. This therapy is carried out by playing Al-Qur'an readings before the baby sleeps. This study aims to examine the effectiveness of murrotal Al-Qur'an therapy on the sleep quality of babies aged 3-6 months. This research uses a quasi-experimental method with a one group pretest-posttest design. The research sample was 16 babies aged 3-6 months with sleep disorders. The results of the study showed that murrotal Al-Qur'an therapy was effective in improving the sleep quality of babies aged 3-6 months. This can be seen from the increase in the average baby sleep quality score from 1.75 in the pretest to 3.25 in the posttest. The improvement in the quality of the baby's sleep can be seen from several indicators, namely: The duration of the baby's sleep has become longer, namely from an average of 7 hours to 8 hours. The baby's frequency of waking up at night decreases, from an average of 2 times to 1 time. Babies fall asleep more easily, from an average of 30 minutes to 15 minutes. Babies are calmer when sleeping, namely from an average of 50% to 75%. Based on the results of this research, it can be concluded that murrotal Al-Qur'an therapy is an alternative therapy that can be used to treat sleep disorders in babies aged 3-6 months.